Mindfulness as an Alternative for Supporting University Student Mental Health: Cognitive-Emotional and Depressive Self-Criticism Measures - Muhammad Abid Azam; Myriam Mongrain; Khushboo Vora; Meysam Pirbaglou; Saam Azargive; Tina Changoor; Noah Wayne; Crissa Guglietti; Alison Macpherson; Jane Irvine; Michael Rotondi; Dawn Smith; et al. (International Journal of Educational Psychology, 2016)
Increases in university-based mental health problems require alternative mental health programs, applicable to students with elevated psychological risks due to personality traits. This study examined the cognitive-emotional outcomes of a university mindfulness meditation (MM) program and their relationship with Self-Criticism (SC), a personality factor linked to depressive vulnerability. University students (n = 71) were assessed at baseline with the Depressive Experiences Questionnaire (DEQ), a measure of depressive personality traits, and two outcome measures: Profile of Mood States (POMS) and Anxiety Sensitivity Index (ASI). Students attending the MM program were reassessed for outcomes at 3 follow up assessments over 2 semesters. Repeated measures analyses of variance revealed improved within-subjects effects with large or very large effect sizes for the subsample that completed the MM program (n = 18) on the POMS Tension-Anxiety, POMS Depression, POMS Fatigue, and Anxiety Sensitivity Index. Multiple linear regression using self-criticism as a predictor of change in depressed mood revealed that higher self-criticism predicted greater reductions in POMS Depression. This study provides evidence for MM-related cognitive-emotional benefits, suggesting that students with elevated self-critical traits may derive exceptional benefits evident in greater reductions of depressed mood.